Diatom assemblage shift driven by nutrient dynamics in a large, subtropical reservoir in southern China. (1st October 2021) - Lei, Yuanda; Wang, Yasu; Qin, Fan; Liu, Juan; Feng, Peijun; Luo, Liancong; Jordan, Richard W.; Jiang, Shijun
Abstract: Anthropogenic eutrophication can significantly alter the nutrient balance in aquatic environments. Changes in nutrient dynamics (nutrient loads and stoichiometry) have profound, usually negative, impacts on aquatic ecosystems, triggering catastrophic regime shift and threatening water resource security and ecosystem sustainability. However, the researches to date have tended to focus on laboratory control experiments or short-term field observations, with few of them using paleolimnological techniques to address long-term effects of changing nutrient dynamics in aquatic ecosystems. Hence, a multi-proxy (diatom and geochemistry) paleolimnological reconstruction, integrated with a 10-year-long monitoring dataset (2001–2012), is developed here to rebuild a 53-year eutrophication history (1959–2012) of the large, subtropical Dashahe Reservoir in South China. Multiple statistical methods consistently revealed a significant ecological change in the reservoir ecosystem during the mid-1980s. Before the shift (1959–1985), both planktonic (e.g. Aulacoseira ambigua and A. granulata ) and benthic (e.g. Encyonema minutum and Gomphonema biceps ) diatoms co-dominated the assemblages with higher diversity, lower biomass and planktonic/benthic diatom ratios (P/B ratios) characterizing a clean water system. After the shift (1986–2012), the planktonic diatoms Aulacoseira and Discostella became overwhelmingly dominant, with lower diversity, higher diatom biomass and P/B ratios typical of eutrophic "polluted" water systems. Despite the apparent dual control by nutrient loadings (N and P) and stoichiometry (N/P), the non-linear relationship between N/P stoichiometry and diatom response roughly fits a typical threshold-like regime shift scenario, suggesting that the diatom assemblage shift occurred mainly in response to a certain threshold N/P ratio (~3.9). These results strongly suggest that nutrient stoichiometry and N overloading should receive more attention in the sustainability management of subtropical reservoir and lake systems. Highlights: Eutrophication process during 1959–2012 was reconstructed in the subtropical Dashahe Reservoir. Paleolimnological reconstruction matches the overlapped monitoring records. A regime shift occurred in mid-1980s in the reservoir. Both nutrient enrichment and stoichiometric change have impacted the diatom succession dynamics. The diatom community shift occurred when a threshold N/P ratio (~3.9) was reached.